Enhancing Tourist Visits to Villages through Branding, Experience, and Digital Promotion: The Role of Value Creation - Iwan Setiawan; Ratih Hurriyati; Heny Hendrayati; Bambang Widjajanta (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Indonesia’s tourism sector holds significant potential to drive economic growth, yet tourist visits remain concentrated in urban destinations, leaving rural areas like the Eastern Priangan region of West Java underexplored. This study aims to examine how destination branding, tourism experience, and digital promotion media influence tourists’ decisions to visit five emerging tourist villages in Eastern Priangan, with tourism value creation as a mediating factor. A quantitative approach was employed, surveying 200 domestic tourists who visited Bayongbong, Taraju, Gunung Sari, Batulawang, or Selasari, supplemented by interviews with ten village tourism managers. The findings reveal that digital promotion media has the strongest influence on visiting decisions, followed by destination branding and tourism experience, with tourism value creation partially mediating these relationships. Villages with active digital campaigns, such as Taraju and Batulawang, showed higher visitor interest. The study concludes that integrated strategies combining consistent branding, authentic experiences, and robust digital promotion are essential for enhancing the competitiveness of rural tourist villages. These findings offer practical insights for village managers and policymakers to strengthen tourism development through improved infrastructure and targeted marketing, fostering sustainable growth in Indonesia’s rural tourism sector.